English Teachers’ Pedagogical Competence in Implementing Kurikulum Merdeka - Syamsiarna Nappu; Hasnawati; Nurdevi Bte Abduh (Balla' Caradde Education, 2026)
This study investigated English teachers’ pedagogical competence in implementing the Kurikulum Merdeka, Indonesia's official curriculum. Pedagogical competence is examined with respect to teachers’ mastery of learning theories and principles, curriculum development aligned with the Kurikulum Merdeka, the organization of educational learning, and assessment and evaluation practices. The study employed a descriptive quantitative design using a questionnaire adapted from the national standards of teacher competence (Permendiknas No. 16 Tahun 2007) and contextualized to the principles of Kurikulum Merdeka. The participants were ten English teachers from junior high schools in Gowa Regency. The findings indicated that teachers demonstrated a very high level of pedagogical competence across all indicators. These results suggested that English teachers are generally well prepared to implement Kurikulum Merdeka, particularly in learner-centered instruction, flexible curriculum planning, and formative assessment practices. The study highlighted the importance of continuous professional development for sustaining and enhancing pedagogical competence in line with the evolving demands of the current curriculum.